(untitled) (LIS TODAY, 2022)
[In library and information management system, Cloud Computing plays a crucial role. The majority of libraries have been digitized and transmitted to internet platforms through manual systems. The majority of Cloud Computing Services have been identified and large amount of computing resources can be deployed in minutes through it. The study’s goal is to talk about how libraries may improve their services. The research has looked into how cloud-based library services can enhance library services. The study’s goals are to discover Cloud Based Application-related Library Services, as well as to identify Cloud Based plat forms-related Library Services. The paper presents some solutions for the problem of “How is the Library services enhanced Cloud based Library Services”. The main point of the study is to discuss objectives like, to find out Cloud Based Applications related Library Services, to identify Cloud Based platforms related to Library Services. to identify Cloud Base free services for Libraries. Secondary data have been used for this comprehensive study. The services are available by Cloud Technology are as storage services. Google Drive, Mega Drive, Dropbox, I Cloud etc. Utilizing cloud-based services, libraries may create library repositories. E-books can be saved and shared with the appropriate users. Professional support is required for library e-book lending services, which include numerous technical infrastructure and business process components. These elements form an ecosystem that allows libraries to secure licenses from companies to lend eBooks. Professional support is required for library e-book lending services, which include numerous technological infrastructure and business process components. Another important service is OPAC sharing. The Internet can be used to share bibliographic information. As a result, the bibliographical information of Networked Automated Libraries is elaborated by their Online Public Assess Catalog. As a result, Cloud Computing plays an important role in improving library and information services.]